2000
DOI: 10.1093/oxfordjournals.aje.a010275
|View full text |Cite
|
Sign up to set email alerts
|

Body Size and Breast Cancer Risk in Black Women and White Women: The Carolina Breast Cancer Study

Abstract: The relation between body size and breast cancer risk was investigated in a population-based, case-control study of Black women (350 cases, 353 controls) and White women (523 cases, 471 controls) from North Carolina, aged 20-74 years in 1993-1996. Logistic regression analyses compared tertiles of each body size variable, adjusting for age and breast cancer risk factors (results shown for highest relative to lowest tertile). Among premenopausal women, body mass index (kg/m2) was inversely associated with breast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
93
2
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(104 citation statements)
references
References 54 publications
8
93
2
1
Order By: Relevance
“…A population-based case-control study that included 350 Black breast cancer cases (Carolina Breast Cancer Study) did not observe an increased risk of postmenopausal breast cancer in women who were overweight or obese; nor did a cohort study of breast cancer mortality (Cancer Prevention Study II; ref. 13). Hospital-based case-control studies yielded conflicting results (10)(11)(12) + .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A population-based case-control study that included 350 Black breast cancer cases (Carolina Breast Cancer Study) did not observe an increased risk of postmenopausal breast cancer in women who were overweight or obese; nor did a cohort study of breast cancer mortality (Cancer Prevention Study II; ref. 13). Hospital-based case-control studies yielded conflicting results (10)(11)(12) + .…”
Section: Discussionmentioning
confidence: 99%
“…Several case-control studies have reported on the relation of obesity to breast cancer risk in African American women separately by menopausal status, with inconsistent results (10)(11)(12)(13)(14). There was little evidence of an association of current body mass index (BMI) with risk of breast cancer in premenopausal women (10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning anthropometry, it is accepted that higher values of body mass index (BMI) are associated with a reduced risk of BC in premenopausal women and with an increased risk in postmenopausal ones (Lahmann et al, 2004;WCRF, 2007). Absence of association in premenopausal women has been also described for certain anthropometric measures in some populations such as Chinese (Shu et al, 2001;Chow et al, 2005), Japanese (Hirose et al, 2001), or African American women (Hall et al, 2000), different from what has been consistently described in the Western and Caucasian societies. Recently, waist-to-hip ratio was also associated with an increase of risk in premenopausal Nigerian (Okobia et al, 2006) and Asian American women (Wu et al, 2007).…”
Section: Introductionmentioning
confidence: 88%
“…Some studies examined regional adiposity and BC risk [4][5][6][7][8][9][10][11] . A positive association of central adiposity with postmenopausal BC risk and also a weaker association for premenopausal women were found in most of these studies.…”
Section: Introductionmentioning
confidence: 99%